2002
DOI: 10.1016/s1470-0328(02)00142-8
|View full text |Cite
|
Sign up to set email alerts
|

Why do women have voiding dysfunction and de novo detrusor instability after colposuspension?

Abstract: Objective To investigate the causes of voiding dysfunction and new detrusor instability after colposuspension.Design Prospective, observational study.Setting Urogynaecology unit, district general hospital.Population Seventy-seven women undergoing colposuspension for genuine stress incontinence. MethodsThe following factors were investigated: 1. bladder neck elevation by magnetic resonance imaging before and after surgery; 2. urethral compression by measuring bladder neck approximation to the pubis with magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Stanton and other groups showed that the modified technique had similar cure rates of 50–80% after 5–20 years4, 5, 9, 10, 12. Nevertheless, 5–50% of the patients develop postoperative urgency symptoms, de novo urge incontinence or residual urine with voiding difficulties6–11, 13. A major problem to be solved is the lack of objective criteria or a standard for determining the optimal level of elevation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Stanton and other groups showed that the modified technique had similar cure rates of 50–80% after 5–20 years4, 5, 9, 10, 12. Nevertheless, 5–50% of the patients develop postoperative urgency symptoms, de novo urge incontinence or residual urine with voiding difficulties6–11, 13. A major problem to be solved is the lack of objective criteria or a standard for determining the optimal level of elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Colposuspension2 continues to be the method of choice and has not been replaced as the gold standard of incontinence surgery by recently introduced operative methods such as tension‐free vaginal tape3. Despite fairly good results after 10 years with a cure rate of 69%4, 5, approximately 20% (range, 5–50%) of women develop bladder voiding disturbance and de novo urge incontinence due to excessive correction6–11. Although some controversy exists12, many investigators agree that excessive correction may lead to voiding dysfunction, urge incontinence, enterocele and rectocele6, 11, 13–16.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unabhängig von der sinnvollen präoperativen lokalen Estrogenisierung zur Verbesserung von Proliferationsgrad, Kollagengehalt und Verbesserung der lokalen Flora sollte bei Frauen im höheren Alter nur eine sparsame Elevation des Blasenhalses angestrebt, jede Überkorrektur vermieden werden [21,22]. postoperative Miktionsstörungen; mit jeder Lebensdekade steigt allerdings das Risiko der funktionellen Obstruktion steil an.…”
Section: Für Alle Inkontinenzoperationen Muss Eine Neue Art Der Bewerunclassified